2003
DOI: 10.1046/j.1365-2842.2003.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between condylar position, joint morphology and craniofacial morphology in orthodontic patients without temporomandibular joint disorders

Abstract: The present study investigated condylar position and joint morphology in adolescent patients and elucidated the possible association between the joint structure and condylar position, and craniofacial morphology. Sixty-five adolescent patients were selected as subjects and their tomograms and lateral cephalograms were analysed. No significant differences in joint spaces were found between the right and left temporomandibular joints. Both the condyles in this population were located slight anteriorly in the gle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 11 publications
2
14
0
1
Order By: Relevance
“…Regarding the posterior articular spaces, there was little statistically significant difference between the right (2.1 ± 0.8 mm) and left (2.3 ± 0.8 mm) sides (Table 2). Kikuchi et al 26 found similar values for anterior (mean, 1.8 mm) and posterior (mean, 2.29 mm) articular spaces, in a sample of adolescents.…”
Section: Discussionmentioning
confidence: 70%
“…Regarding the posterior articular spaces, there was little statistically significant difference between the right (2.1 ± 0.8 mm) and left (2.3 ± 0.8 mm) sides (Table 2). Kikuchi et al 26 found similar values for anterior (mean, 1.8 mm) and posterior (mean, 2.29 mm) articular spaces, in a sample of adolescents.…”
Section: Discussionmentioning
confidence: 70%
“…Several imaging modalities have been proposed to evaluate the condylar position in the glenoid fossa, including conventional radiography (Jos e Pereira et al, 2004;Serra and Gavião, 2006), conventional tomography (Major et al, 2002;Kikuchi et al, 2003;Wiese et al, 2008), CT (Tsuruta et al, 2004;Okur et al, 2012), CBCT (Ikeda and Kawamura, 2009;Ikeda et al, 2011;Cho and Jung, 2012;Ikeda and Kawamura, 2013), and MRI (Incesu et al, 2004;Robinson de Senna et al, 2009;Kandasamy et al, 2013). Conventional radiography, especially transcranial radiography which was previously used to assess condylar position and morphology, represents only the lateral pole of the condyle.…”
Section: Discussionmentioning
confidence: 99%
“…The first was the best-fit line method that was the angle between Ebf and Frankfort horizontal ( Figure 2); the second was the top-roof line method that was the angle between Etr and Frankfort horizontal ( Figure 3). [7][8][9][10][11][12][13][14][15][16] The eminence height was established by the measurement of the perpendicular Figure 1 Lines and angles used in the study. Ebf, eminence inclination best-fit line; Etr, eminence inclination top-roof line; Eh, eminence height distance between the lowest point of the articular eminence and the highest point of the fossa ( Figure 4).…”
Section: Measurementsmentioning
confidence: 99%
“…The inclination of articular eminence varies among people and it dictates the path of condylar movement as well as the degree of rotation of the disc over the condyle. 1,2 Many methods are used to examine the inclination of articular eminence, such as measurements on dry skulls, [3][4][5] conventional radiography 6 and tomography, 1,7 MRI [8][9][10][11] and CT. [12][13][14] However, CT machines have limitations in dentistry because of their high cost, large footprint and high radiation exposure. Cone beam CT (CBCT) has recently been developed as an alternative to conventional CT for dental and maxillofacial diagnostic osseous tasks.…”
Section: Introductionmentioning
confidence: 99%